Factors associated with undiagnosed hypertension among Tongan adults: a cross-sectional study - Seini Siahi Talanoafoou Fifita; Daisuke Nonaka; Mele Tilema Cama; Mele Inu Filise (Tropical Medicine and Health, 2024)
Abstract Background Hypertension is responsible for many premature deaths worldwide. However, many individuals with hypertension remain undiagnosed. Tonga is one of the countries that has had a steep increase in hypertension, thus undiagnosed hypertension could also be increasing. Purpose of this study was to assess the prevalence and factors associated with undiagnosed hypertension among Tongan adults. Methods This cross-sectional study used data collected from conveniently sampled 473 participants using electronic questionnaire and digital sphygmomanometer through household visits between February and March 2023. Inclusion criteria were age of 18–65 years, residence in the villages for at least six months, and not being pregnant. Fisher’s exact test and mixed-effect logistic regression were performed using the EZR software to assess the association between undiagnosed hypertension and predictor variables. Results The prevalence of undiagnosed hypertension was 22.4% (106/473). Five variables that were significantly associated with undiagnosed hypertension in Fisher’s exact test were included in the multivariate logistic regression. Overall, only three variables remained significant. First, participants who never had their blood pressure measured had higher prevalence compared to those who had it checked recently (33.3% vs. 19.1%); odds ratio: 2.24). Secondly, participants who were not aware of the risk of developing hypertension were significantly more likely to have undiagnosed hypertension compared to those who were aware (27.9% vs. 16.7%; odds ratio: 1.81). Lastly, middle-aged participants (30–49 years) and older (50–65 years), were significantly more likely to have undiagnosed hypertension compared to those who were 18–29 years old (30.0% and 23.7% vs. 11.8%; odds ratio: 3.58 and 3.38 vs. 1.00). Conclusion The prevalence of undiagnosed hypertension could be substantial among Tongan adults, implicating a need to address this issue by doing further research and review current public health work to address hypertension in Tonga. Undiagnosed hypertension was associated with having no experience of blood pressure measurement, lack of awareness about hypertension, and age. Tongan government should provide people with more opportunities to have their blood pressure measured and to improve their awareness.